Change Management in Organizations under Conditions of Uncertainty - Ясіньска, Йоанна; Браніцкий, Мілош (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2018)
This article analyzes the problems of struggle with uncertainties during the changes in management processes., analyzes new concepts and methods of monitoring the unpredictable future in strategic terms, drawing attention to the conflicting strategies are classics from the standpoint of management, reinterpreted some changes in management strategy in situations of uncertainty, which is necessary due to the increasing complexity and unpredictability of events in the organizational environment.